Leading business change : a practical guide to transforming your organization - Stumpf, Karin (CRC Press, 2015)
Most books dealing with change management focus on how companies reach their corporate goals, instead of on what individual leaders must do. Filling this need, Leading Business Change: A Practical Guide to Transforming Your Organization is an easy and fun read that will inspire you to think more closely about how you implement change as a leader. The book presents a proven approach to help leaders of global initiatives grapple with impossible projects and deliver on their goals. The first part of the book explains the author's approach to change management, centering on the need not just for an.